2020
DOI: 10.1590/1678-4499.20190380
|View full text |Cite
|
Sign up to set email alerts
|

Selection to high productivity and stink bugs resistance by multivariate data analyses in soybean

Abstract: Stink bugs that affect soybeans are responsible for significant losses in seed production, quality and germination potential, in addition to hindering the mechanized harvest. To develop insect resistant materials, the breeder can compile a selection index by factor analysis. Therefore, the objective of this work was to validate the use of factor analysis, by means of its estimated gains, for the selection of highly productive and stink bugs resistant genotypes in two soybean segregating populations. For this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
6
1
2
Order By: Relevance
“…Finally, the distance from a given genotype to the ideotype could be computed using the Euclidean distance. So, in contrast to conclusions of recent studies (Bermudez & Pinheiro, 2020), we have shown here that factor analysis is an efficient technique to establish an index in which most of the traits are selected favorably, showing satisfactory gains for the application in breeding programs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, the distance from a given genotype to the ideotype could be computed using the Euclidean distance. So, in contrast to conclusions of recent studies (Bermudez & Pinheiro, 2020), we have shown here that factor analysis is an efficient technique to establish an index in which most of the traits are selected favorably, showing satisfactory gains for the application in breeding programs.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though the SH index is widely used as a multi-trait selection index in plant breeding trials, there has been evidence (Bhering et al, 2012) that the adoption of this index is not interesting for plant breeding. Since the combination of multivariate techniques is efficient to account for the multicollinearity issue in multi-trait indexes (Rocha, Machado, & Carneiro, 2018), there would seem to be value in an investigation to develop an index that covers the weaknesses of the SH index in which all the traits are selected favorably and with satisfactory gains for the application in breeding programs (Bermudez & Pinheiro, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Factor analysis has already been used as a selection index in several studies (Barbosa et al., 2019; Bermudez & Pinheiro, 2020; Filipović et al., 2014). Based on this analysis, we aimed to clarify the specific factors that explained the set of analyzed variables.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analyses are used to classify genotypes into distinct groups, such that genotypes that constitute the same group have similar characteristics, whereas genotypes in different groups are distinct (Darkwa et al., 2020). Conversely, factor analysis is a powerful tool used to explain the relationship between numerous variables, reducing the trait complexity by defining a smaller set of dimensions, called factors, which can then be used as a selection index (Barbosa et al., 2019; Bermudez & Pinheiro, 2020; Filipović et al., 2014; Mair, 2018). In this sense, the objective of this study was to identify the key traits and genotypes of carioca common beans with high NUsE using multivariate statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Para o caráter TOL foi necessário realizar a análise individual dos experimentos devido à não homogeneidade dos resíduos entre os dois experimentos. Pode-se observar uma diferença no CV entre os experimentos, já que em 2019/20 foi de 13,40 e em 2020/21 foi de 3,27, o que é um indício de maior influência do ataque de percevejos no primeiro ano (BERMUDEZ; PINHEIRO, 2020;FERNANDES et al, 2019;ROCHA et al, 2014). A média também foi distinta para os dois anos agrícolas, sendo 68,51 na primeira e 90,87 na segunda e mesmo havendo essa diferença na expressão da TOL, houve diferença significativa para o efeito de genótipos em ambos os experimentos realizados.…”
Section: Análise De Variância E Herdabilidadeunclassified